Failures East and West : cultural encounters between East Asia and Europe - Hertel, Ralf, 1973-; Sandrock, Kirsten A. (Edinburgh : Edinburgh University Press, 2023)
Bringing together scholars working across Chinese Studies, Japanese Studies, English Studies and French Studies, this book presents new perspectives on instances of failed intercultural encounters by theorizing epistemologies of failure.
8 Barthes and Bouvier in Japan: The Difficult Dialogue between Semiotics and Intercultural Communication -- 9 Between Failure and Empowerment: Historicity, Genre and Cultural Clashes in David Mitchell's The Thousand Autumns of Jacob de Zoet -- 10 Marx between East and West: The Karl Marx Statue in Trier as an Example of Intercultural Failure? -- Index
Includes bibliographical references and index.
Description based on print version record.
In English.
JSTOR
Keywords: Cultural relations in literature; Failure (Psychology) in literature; Europe -- Relations -- East Asia; East Asia -- Relations -- Europe; Relations culturelles dans la littérature.; Échec dans la littérature.; HISTORY / Asia / General; Cultural relations in literature; Failure (Psychology) in literature; International relations; East Asia; Europe